The Improved Overhearing Backup AODV Protocol in MANET - Elham Zamani; Mohammadreza Soltanaghaei (Journal of Computer Networks and Communications)
Mobile ad hoc network (MANET) is one of the most widely used networks, which has attracted attentions, having features such as limited energy resources, limited bandwidth, and security weaknesses due to lack of a central infrastructure. Safe and suitable routing is one of the research aspects of MANET. In this paper, a proposed method, called M-AODV, which is a type of overhearing backup protocol, based on AODV, is presented. The simulation results of this protocol, applied by NS2 simulator, showed the improvement of packet delivery rate and reduction of overhead and delay. Moreover, to assess the security of the proposed protocol, we simulated M-AODV and AODV protocols under black hole and wormhole attacks, using no security solution. The results showed that M-AODV had been improved in terms of packet delivery ratio, and the delay had been reduced as well, but the amount of overhead had been increased.